Irrigation, Nutrition, and Citrus Fruit Quality - Mongi Zekri; Thomas A. Obreza; Robert Koo; Fernando M. Alferez (EDIS)
This 3-page publication targets agricultural and horticultural producers, homeowners, Extension agents, industry or governmental staff, land managers, other professionals, youth and interested citizens. It is a minor revision written by Mongi Zekri, Thomas A. Obreza, Robert Koo, and Fernando M. Alferez, and published by the Soil and Water Science Department, April 2018.